Schoolaboration: Effort to improve students’ skills in creating social media content in SMA Muhammadiyah Muntilan - Fadillah Sandy; Annis Azhar Suryaningtyas; Prihatin Dwihantoro; Dwi Susanti; Lintang Muliawanti (Universitas Muhammadiyah Magelang, 2023)
Digital literacy includes not only the ability to find and share information, but also the skills to create digital content. These activities aim to improve the creativity and build content on social media. As a response to this phenomenon, a school collaboration program was conducted at SMA Muhammadiyah 1 Muntilan. The program included a socialization and training on social media content. The socialization discussed the basic concepts of content on social media, including content selection, consistency, and timing. The results of these activities are the improvement of digital content creativity and 20 videos of school’s profile created by students of SMA Muhammadiyah 1 Muntilan.